Connectivity as a tool in the prioritization and protection of sub-urban forest patches in landscape conservation planning - Pirnat, Janez; Hladnik, David (Landscape and urban planning, 2016)
•The structure of forest patches and their spatial distribution are benevolent.•Spatial distribution of urban forests in Ljubljana is still favourable.•The real fragmentation occurred during the construction of the highway beltline.•Connectivity changes and nature preservation can be presented by a spatial model.•Connectivity among forest cores is an important index of habitat conditions. Urbanisation development influences surrounding landscape processes, which are reflected by landscape structural patterns. Forest areas are often regarded as a spatial reserve for present and future urbanisation needs, while at the same time they often represent the last remnant of natural environment. In the present research we analysed (1) the change in forest cover in the area of suburban forests of Ljubljana between 1975 and 2012, (2) the connectivity and conservation buffers as one of the foundations for the assessment of biodiversity functions. Between 1975 and 2012, all the forests with important cores were subject to clearings for settlement- and agricultural purposes, but clearing usually did not extend beyond forest edges. The real fragmentation occurred during the construction of the highway beltline. In the area of Ljubljana, connectivity changes and connectivity loss in two different time periods are presented by a spatial model based on the Graph Theory which can also be used in spatial planning. Due to the high percentage of forest cover and the favourable distribution of forest patches and cores around the city of Ljubljana, no connection is currently in danger; the weakest link is stretching from the centre of Ljubljana towards the southeast. In the process of evaluating the biodiversity of urban forests, it will be necessary to add connectivity among forest cores as an important index while evaluating the favourable conditions of different habitat types.